Critical public archaeology : confronting social challenges in the 21st century - Westmont, V. Camille
Critical approaches to public archaeology have been in use since the 1980s, however only recently have archaeologists begun using critical theory in conjunction with public archaeology to challenge dominant narratives of the past. This volume brings together current work on the theory and practice of critical public archaeology from Europe and the United States to illustrate the ways that implementing critical approaches can introduce new understandings of the past and reveal new insights on the present. Contributors to this volume explore public perceptions of museum interpretations as well as public archaeology projects related to changing perceptions of immigration, the working classes, and race